Structure of superheavy nuclei - N. V. Antonenko; G. G. Adamian; A. N. Bezbakh; V. G. Kartavenko; L. A. Malov; T. M. Shneidman; N. Yu. Shirikova; A. V. Sushkov; R. V. Jolos (Eurasian Journal of Physics and Functional Materials, 2021)
A short review of the results on the structure of superheavy nuclei is presented.